Pengaruh profitabilitas, non-debt tax shield dan karakteristik perusahaan terhadap struktur modal - STELLA STELLA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The purpose of the study is to get empirical evidence about the effect of profitability, non-debt tax shield, asset structure, size, age, growth and risk on capital structure. The sampling technique used in this research is purposive sampling. The analysis methods are multiple regressions analysis. The research result showed that the effect of profitability, age, growth and risk on capital structure is significant. While, the effect of non-debt tax shield, asset structure and size on capital structure is not significant.